Social Media, New Cultures, and New Threats: Impact on University Students in Bangladesh - Ashfaq Ferdous; Zeenat Huda (Human Behavior and Emerging Technologies)
In addition to its use as an effective means of communication, the versatility of social media—probably the most salient technological development of recent times—has gradually increased its popularity over the years. But while it has been instrumental in the emergence of numerous new cultures, the use of social media has also posed a number of threats to individuals, societies, countries, and the world as a whole. It has been revealed through various literature reviews that no specific research has been done before on social media regarding its ability to simultaneously create new cultures and new threats. Therefore, the current research was conducted among university-level students in Bangladesh keeping this issue in mind. The study was designed in light of an appropriate theoretical framework, and as part of the quantitative method, an online survey was carried out to collect data from 217 university students who are studying at different public and private universities in the country. Besides, case studies were administered to 20 students for in-depth understanding. Findings uncovered that most romantic relationships formed through social media are problematic and many people have had bad experiences with such relationships. Most participants are victims of cyberstalking and varied forms of harassment and social stigma. In spite of being an epoch-making medium for education, its use is also responsible for the poor academic performance of many students, and despite its emergence as a new platform for journalism, social media has boosted yellow journalism as well. While its use in product marketing has grown exponentially and shown considerable positive impact, consumer fraud has also become common. Furthermore, although the number of social media entrepreneurs is constantly increasing and many are succeeding, the number of failures is not insignificant. It is evident from the research that the negative impact of social media use is expanding day by day in new directions, and it is urgent to ensure its proper use for the greater good.